Features of feeding for pacific herring Clupea pallasii, walleye pollock Theragra chalcogramma, and arabesque greenling Pleurogrammus azonus in Peter the Great Bay (Japan Sea) in summer season - Olga I. Pushchina; Sergey F. Solomatov; Boris M. Borisov (Известия ТИНРО)
Qualitative and quantitative indices of feeding and competitive relationships are investigated for pacific herring Clupea pallasii , walleye pollock Theragra chalcogramma , and arabesque greenling Pleurogrammus azonus on the data of bottom trawl surveys conducted over the shelf and upper continental slope of Peter the Great Bay in June-September of 2002-2009. Daily rations of these species in summer are estimated as 4.5, 3.0 and 4.3 % of body weight on average, respectively. The diet depends on their bathymetric distribution and structure of prey: generally, the portion of plankton and nektobenthos reflects the species ability to dwell beyond the bottom and changes from 66.9 and 32.1 % for herring and 45.2 and 46.9 % for pollock to 30.2 and 31.8 % for greenling. The rest of the greenling diet is presented by benthic invertebrates (24.8 %) and nekton (13.2 %). Mysids are the main common diet component for all three species, their portion in the herring and pollock diets is extremely high in Peter the Great Bay comparing with other habitats of these species, obviously because of high abundance of mysid shrimps and low concentrations of large-sized zooplankton (particularly euphausiids) in the Bay. Role of the considered species in demersal ichthyocenosis of Peter the Great Bay is not high enough for food competition between them, taking into account their active seasonal migrations and low stocks of herring and pollock in recent times.